Impacts of flexible conditions on factory work experience: a study case in a metallurgy of ABC's region of São Paulo State (Cadernos de Psicologia Social do Trabalho, 2009)
The focus of this article is to discuss the impact of nowadays' transformations of the factory work context on the work experience and on the suffering caused by its organization. We are going to present a study case ran in a metallurgy of ABC's region of São Paulo State. The methodology used was field research in participant observation regime. Through the use of field diary writings, episodes and observations that seemed to better describe the experience of work were collected. We aimed to compare the collected data in the research field with the literature related to the description of nowadays transformations in the factory work management. This discussion puts an end to a polemic: Do the new forms of factory work management allow a bigger participation of the worker in the work itself or there are still rigid forms of control and separation between conception and execution of the work? The empirical data leads us to conclude that the work organization still relies on a technical system that adds separation between conception and execution to a vigilant and controlling system of the factory activities. Besides theses factors, the new forms of precarization and flexibilization of the labor contract regime are added to the suffering in work.